Radiation therapy and PD-1/PD-L1 blockade: the clinical development of an evolving anticancer combination - Gong, Jun (J Immunother Cancer, 2018)
Several inhibitors of programmed cell death-1 (PD-1) and programmed death ligand-1 (PD-L1) have been approved as a form of immunotherapy for multiple cancers. Ionizing radiation therapy (RT) has been shown to enhance the priming and effector phases of the antitumor T-cell response rendering it an attractive therapy to combine with PD-1/PD-L1 inhibitors. Preclinical data support the rational combination of the 2 modalities and has paved way for the clinical development of the combination across a spectrum of cancers. In this review, we highlight the preclinical and clinical development of combined RT and PD-1/PD-L1 blockade to date. In addition to a comprehensive evaluation of available safety and efficacy data, we discuss important points of consideration in clinical trial design for this promising combination.